2009
DOI: 10.1111/j.1365-2966.2009.15668.x
|View full text |Cite
|
Sign up to set email alerts
|

Unusual glitch activity in the RRAT J1819−1458: an exhausted magnetar?

Abstract: We present an analysis of regular timing observations of the high magnetic field Rotating Radio Transient (RRAT) J1819−1458 obtained using the 64‐m Parkes and 76‐m Lovell radio telescopes over the past 5 years. During this time, the RRAT has suffered two significant glitches with fractional frequency changes of 0.6 × 10−6 and 0.1 × 10−6. Glitches of this magnitude are a phenomenon displayed by both radio pulsars and magnetars. However, the behaviour of J1819−1458 following these glitches is quite different to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
98
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(113 citation statements)
references
References 28 publications
15
98
0
Order By: Relevance
“…From the figure, there is no evidence that the intensity of bimodal bursts undergoes obvious deviation. As reported by Lyne et al (2009) and shown in Fig. 4 (bottom), the timing residuals of RRAT J1819−1458 fall into a triband distribution.…”
Section: Data Analysis and Resultssupporting
confidence: 71%
“…From the figure, there is no evidence that the intensity of bimodal bursts undergoes obvious deviation. As reported by Lyne et al (2009) and shown in Fig. 4 (bottom), the timing residuals of RRAT J1819−1458 fall into a triband distribution.…”
Section: Data Analysis and Resultssupporting
confidence: 71%
“…Using the Xronos package, we folded both X-ray data sets using the radio ephemeris (Lyne et al 2009), confirming the sinusoidal X-ray modulation found with XMMNewton (McLaughlin et al 2007) and Chandra ). In addition, we performed a periodicity search obtaining a Pspin=4.26328(6) s (epoch= MJD 54 617), in agreement with previous work.…”
Section: Timingsupporting
confidence: 60%
“…The spin period of RRAT J1819-1458 is 4.3 s (Ṗ ∼ 3.2×10 −13 s s −1 ; Lyne et al 2009), with a characteristic age of 117 kyr and a dipolar magnetic field of B ∼5×10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These time scales considerably differ from those observed in PSR B1931+24 and PSR J1841-0500. According to Lyne et al (2009), rotating radio transients could be exhausted magnetars. Most of them occupy the region of the P-Ṗ diagram with periods of several seconds andṖ higher than 10 −14 , although one is surprisingly found in the region of normal radio-pulsars.…”
Section: Introductionmentioning
confidence: 99%